Impact on lung function among children exposed to home new surface materials: The seven Northeastern Cities Study in China. (1st March 2019) - Hu, Li‐Wen; Gurram, Namratha; Bloom, Michael S.; Qian, Zhengmin; Howard, Steven W.; Iwelunmor, Juilet; Zeeshan, Mohammed; Lin, Shao; Yang, Bo‐Yi; Zeng, Xiao‐Wen; Liu, Kang‐Kang; Hu, Qian‐Sheng; et al.
Abstract: We conducted a cross‐sectional study to investigate the associations between recent home renovation exposure and lung function in children. We randomly recruited 7326 school children residing in 24 districts from seven cities in northeastern China. We collected information about home renovations from parents using a questionnaire and lung function measurements from children using spirometer recordings gathered by trained professionals and expressed as the forced expiratory volume in 1 second (FEV1), forced vital capacity (FVC), maximal mid‐expiratory flow (MMEF), and peak expiratory flow (PEF). We identified higher odds of diminished lung function among these with home renovation in the previous 2 years compared to those without home renovation in the previous 2 years, for FVC (odds ratios [ORs] = 1.84 [95%CI: 1.58, 2.15]; FEV1: ORs = 2.82 [95%CI: 2.36, 3.36]; PEF: ORs = 1.51 [95%CI: 1.24, 1.83]; and MMEF: ORs = 1.90 [95%CI: 1.60, 2.24]). The associations were stronger among children exposed to new polyvinyl chloride (PVC) flooring compared to children exposed to other surface materials. Our results were consistent throughout the analysis of each type of renovation materials. In conclusion, recent home renovation exposure was associated with poor lung function among children. Strategies to protect home owners and their families from respiratory hazards during and after renovation are required.